2013
DOI: 10.5505/ptd.2013.92905
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the morphology and motility of spermatozoa: relation with total sperm count

Abstract: Purpose: The aim of this study was to investigate the differences in sperm morphology and motility in patients with different sperm counts, and to search the influence of sperm morphology over sperm motility. Materials and methods:We evaluated semen analysis of 1174 males admitted to infertility clinic using "Makler counting camber" for evaluation of number and motility, and strict criteria (Kruger-Tyberg) for the morphological assessment. According to total sperm count, patients were divided into three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Morphologically normal sperm besides the concentration and motility of sperm are good indicators of semen quality, as ability to fertilize the oocyte (17). Morphological normal sperms with low rate have been correlated with lower infertility rate in males (18).This was in contrast with the results of this study, as the MNS showed a significant increase using activation techniques especially in the DGC with TAD 600mg Glutathione. In addition to that, the components of liquid artificial medium may improve the percentage of MNS and progressive motility because it dilute and reduce the semen viscosity (16).…”
Section: Discussioncontrasting
confidence: 94%
“…Morphologically normal sperm besides the concentration and motility of sperm are good indicators of semen quality, as ability to fertilize the oocyte (17). Morphological normal sperms with low rate have been correlated with lower infertility rate in males (18).This was in contrast with the results of this study, as the MNS showed a significant increase using activation techniques especially in the DGC with TAD 600mg Glutathione. In addition to that, the components of liquid artificial medium may improve the percentage of MNS and progressive motility because it dilute and reduce the semen viscosity (16).…”
Section: Discussioncontrasting
confidence: 94%
“…The resulting percentage of abnormal spermatozoa as well as specific structural abnormalities may serve as an indicator of a defective mechanism related to spermatozoa production and/or maturation [ 1 ] and is a valuable predictor of spontaneous pregnancies and fertilization success in assisted reproductive technology (ART) [ 7 - 9 ]. Furthermore, abnormal spermatozoa morphology has been linked not only to a decrease of traditional parameters of semen quality [ 10 - 12 ] but also to an increase in contemporary markers of sperm damage, such as DNA fragmentation [ 1 , 2 ] or reactive oxygen species (ROS) overproduction [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…They studied that sperm morphological defects increases with decreasing sperm count. 33 Only few studied the defects with normal sperm counts also. 34 Defects in the head are the most common defects.…”
Section: Figure 1: Distribution Of Cases In Different Sperm Count Gromentioning
confidence: 99%
“…These defects increase with decreasing sperm count. 33 Amorphous head is a defect with genetic aberration, so this is a severe form and incapable of fertilization. Globozoospermia small round head with no acrosome are also genetically determined and due to the absence of acrosin unable to bind to zona pellucida.…”
Section: Figure 1: Distribution Of Cases In Different Sperm Count Gromentioning
confidence: 99%